1996
DOI: 10.1007/s002800050563
|View full text |Cite
|
Sign up to set email alerts
|

The effects of terbium on the cellular accumulation of cisplatin in MDA-MB-231 human breast tumor cells

Abstract: In agreement with earlier studies, the plasma membrane of MDA cell lines contain a specific Tb(3+)-binding protein. Our findings suggest that the Tb(3+)-binding protein may be intimately associated with the accumulation of DDP in breast tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…This suggests that the enhancement of cisplatin cytotoxicity by DPM in MDA/R cells employ a mechanism that does not involve an increase in the cellular accumulation of cisplatin. Mack et al 27 , have suggested that cisplatin resistance in MDA-MB-231 human breast cancer cells may in part be due to an increase in the detoxification of cisplatin via elevated levels of glutathione. The enhancement of DNA repair is a cellular response to cisplatin resistance and, to achieve higher levels of resistance, the cell induces mechanisms that affect drug accumulation and/or detoxification 28 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the enhancement of cisplatin cytotoxicity by DPM in MDA/R cells employ a mechanism that does not involve an increase in the cellular accumulation of cisplatin. Mack et al 27 , have suggested that cisplatin resistance in MDA-MB-231 human breast cancer cells may in part be due to an increase in the detoxification of cisplatin via elevated levels of glutathione. The enhancement of DNA repair is a cellular response to cisplatin resistance and, to achieve higher levels of resistance, the cell induces mechanisms that affect drug accumulation and/or detoxification 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they are resistant to CDDP [26]. This has lead to their use as a model to study cisplatin resistance in general and, more specifically, cisplatin resistance in triple-negative breast cancers [2729]. …”
Section: Introductionmentioning
confidence: 99%
“…These findings imply that the receptor binding of Tb 3+ can modulate the cytotoxic activity of cisplatin. It is notable that by the action of Tb 3+ , more cisplatin was accumulated in cisplatin-resistant MDA cells than in cisplatin-sensitive ones [58]. The defective accumulation of DDP has been shown to be a prominent feature in many DDP-resistant cell lines.…”
Section: Enhancement Of the Anticancer Activity Of Cisplatinmentioning
confidence: 99%
“…The defective accumulation of DDP has been shown to be a prominent feature in many DDP-resistant cell lines. In an effort to circumvent this problem, it was examined the cellular accumulation of DDP was determined in the presence of terbium (Tb 3+ ) [58]. The authors also examined the effects of verapamil on the cellular accumulation of DDP in order to delineate the specific interaction of Tb 3+ and DDP.…”
Section: Enhancement Of the Anticancer Activity Of Cisplatinmentioning
confidence: 99%